Actual delivered dose calculation on intra-irradiation cone-beam computed tomography images: a phantom study. (13th January 2021) - Iramina, Hiraku; Nakamura, Mitsuhiro; Mizowaki, Takashi
Abstract: Cone-beam computed tomography (CBCT) images acquired during volumetric modulated arc therapy (VMAT; ii-CBCT) can be used to calculate actual delivered doses (ADDs). However, such ii-CBCT images are degraded by scattered megavoltage x-rays (MV-scatters). We aimed to evaluate the dose calculation accuracy of the MV-scatter uncorrected or corrected ii-CBCT images acquired during VMAT deliveries. For MV-scatter correction on concurrent kilovoltage projections ( P MVkV ), projections consisting only of MV-scatters ( P MVS ) were acquired under the same MV beam parameters and gantry angles and subtracted from P MVkV ( P MVScorr ). In addition, the projections by kilovoltage beams were acquired for reference ( P kV ). The corresponding CBCT images were reconstructed using the Feldkamp–Davis–Kress algorithm (CBCTMVkV, CBCTMVScorr, and CBCTkV as reference). A multi-energy phantom with rods of various relative electron densities (REDs) was used to generate a CBCT-number-to-RED conversion table. First, CBCTkV was reconstructed. Then, the mean CBCT-numbers within each rod were extracted, and a reference table was generated. Concurrent kilovoltage imaging with various field sizes was also demonstrated, and CBCTMVkV and CBCTMVScorr were reconstructed. The extracted CBCT-numbers of each ii-CBCT image were converted into REDs using the reference table. Next, the absolute differences of RED between the ii-CBCT image and CBCTkV were calculated. Ten VMAT plans using a 10 MV flattening-filter-free beam were used for concurrent imaging of an anthropomorphic torso phantom. Moreover, an iterative reconstruction algorithm (IRA) was used for CBCTMVScorr . The plans were recalculated for the corresponding CBCTMVkV, CBCTMVScorr, CBCTMVScorr+IRA, and CBCTkV with the reference table. Finally, the doses were evaluated using 3D gamma analysis (1%/1 mm). The median difference ranges between CBCTMVkV /CBCTMVScorr and the reference values were −0.58 to −0.10/−0.03 to 0.00. The median gamma pass rates of the doses on CBCTMVkV, CBCTMVScorr, and CBCTMVScorr+IRA to the rate on CBCTkV were 70.4, 99.5, and 98.2%, respectively. CBCTMVScorr were comparable with CBCTkV for calculating the ADD from VMAT.